Pengaruh Gaya Belajar Siswa Terhadap Prestasi Belajar Matematika Siswa - Sari, Nuniek Pradita (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstactÂ This study aimed to determine the effect of students´ learning styles toward mathematics achievement. The Subjects of this research were 61 students at SMA N 5 Yogyakarta in eleventh grade. The data collection tools of this research used a learning styles scale. Analysis of the statistical method used anova one way technique. Overall computational data were processed with SPSS 16.0 for windows.Â  Data analysis showed F = 1.993 and p = 0.146 with a significance level (p <0.05) suggesting that there is no influence students´ learning styles to learning mathematics achievement. This means that the hypothesis is rejected. categorization, including low academic achievement. the categorization ofÂ  students´ learning styles at SMA N 5 Yogyakarta are auditory and kinesthetic.Â Keyword: Studentâs Learning Style, Mathematic Achievement